Effectiveness of Assertive Skills Training on Improvement of Assertion and Self-esteem of Third to Fifth Grade Low-assertive Girl Students in Tehran - Y. Rezapour Mirsaleh; P. Aboutorabi Kashani; S. Ebrahimi Ghavam (روانشناسی بالینی و شخصیت, 2013)
The aim of the present study was to investigate the effect of educating self-assertive skills on improvement of assertiveness and self-esteem of third- to fifth-grade girl students with low assertion in Tehran. For this purpose, one region was randomly selected among regions of Tehran through cluster sampling method and tow schools were randomly select-ed among girl primary schools located in this region. Finally, among 27 low assertive students identified by researchers, 20 ones were randomly selected and were randomly divided to experimental and control groups. The design of this study was pre-post test on control group. The Gambrill-Richey Assertion Inventory was used to assess the general as-sertiveness skills, and Cooper-Smith self-esteem inventory was used to assess self-esteem of these students. Following pre-test administration, the assertive skills were educated in a 1.5-hour session per week for 10 weeks and post-test was administered at the end. To assess the effect of assertive skills training, the test was re-conducted for two groups after 25 days. The data were analyzed with two-factor ANOVA with repeated and frequent measurements on one factor. The results indicated that assertiveness and self-esteem of students were improved at the end of survey.  The result of follow-up test revealed that the effect of education was durable after 25 days. According to the results of this study, education of assertive skills can improve assertiveness and self-esteem of students with low assertion.